Male and female witnesses of mobbing: Gender difference in experiencing consequences. A cross-sectional study in an italian sample. (2nd January 2021) - Acquadro Maran, Daniela; Zedda, Massimo; Varetto, Antonella
Abstract: This study aims to analyze, from a descriptive point of view, the impact of the mobbing phenomenon in male and female self-declared witnesses and the consequences that affect it. To better understand the impact of the phenomenon, a comparison was made among witnesses and non-witnesses. The hypotheses were as follows: i . witnesses are predominantly male; ii. witnesses perceived a higher risk of mobbing than non-witnesses and, as a consequence, iii . witnesses experienced more health problems and work-related stress than non-witnesses. Participants were 574 individuals (43.4% witnesses), 254 (44.3%) male and 320 (55.7%) female. They completed a questionnaire about the risk of mobbing in their organization, the perceived psychological functioning and the perceived work-related stress. Findings showed that male and female witnesses indicated the presence of verbal, physical and psychological violence that characterized the relationship within the organization, the presence of interference in individuals' private life and/or the presence of excessive control, isolation, remittance, and deskilling that affected their colleagues more often than female non-witnesses did. About perceived health and work-related stress, findings showed that male and female witnesses perceived a higher severity level of mental health problems than non-witnesses. Results from this research could be useful in improving prevention and intervention programmes that permit possible witnesses of mobbing to understand that consequences affect not only victims but also their perceived health, increasing perceived work-related stress.